CODESRIA Bulletin Online, No. 7, March 2022 - Russia’s invasion of Ukraine: What does it mean for Africa? - Bangura, Yusuf (CODESRIA Bulletin, 2022)
Russia’s invasion of Ukraine marks a decisive end to the post-Cold War security regime that has governed the strained but stable relations between the West and Russia and guaranteed the independence of East European countries and former Soviet republics over the last three decades. The invasion threatens the security of small nations and reinforces the illiberal turn in world politics by challenging the body of rights and democratic norms that gained ascendancy in the 1990s. African opinion- and policy-makers should understand what this portends for the continent. Russia’s transition from communism to capitalism was messy: its economy contracted by about 40 per cent after a shock therapy of price liberalisation and privatisation, inflation skyrocketed, the ruble plummeted, and shortages of basic food items became the norm. While the employment data did not show any mass layoffs, about a quarter of the workforce was on unpaid or low-paid leave. A third of the population fell into poverty and the social protections developed in the Soviet era proved insufficient for maintaining basic wellbeing. Boris Yeltsin, the first post-communist president, sought and Russia was granted membership of the IMF in 1992 and obtained a series of loans with tough conditionalities that did not improve the country’s economy (Gould-Davies and Woods 1999; Crotty 2020). Indeed, former Russian foreign minister and prime minister, Yevgeny Primakov, believes that Russia’s losses under the IMF were twice as large as those suffered during World War II (Arkangelskaya and Shubin 2013). Many Russians saw the IMF loan agreements as an attack on Russia’s sovereignty (Gould-Davies and Woods 1999) and an attempt to turn Russia into a vassal state of the West. Indeed, the loss of the Soviet republics, the deep economic recession, and dependence on Western institutions for finance profoundly weakened Russia’s status as a global power and provoked a conservative and neonationalist turn in domestic politics. Russians yearned for a strong leader who would reverse the decline and restore the country’s position in the comity of nations. After winning several fairly credible elections and stabilising the economy with the help of soaring oil and gas prices, Vladimir Putin, an ex-KGB official, fit the bill of a new messiah. When Putin assumed power in 2000, Russia’s political system, though fragile, could still be described as an electoral democracy in that relatively free and competitive elections were regularly held. However, within a few years of his rule, Putin reined in independent political organisations, developed the brutal tactic of poisoning his key critics, controlled national television stations and other media, weakened the power of the oligarchs who had been empowered by fire sales of state assets, and concentrated power in the presidency (McFaul 2021). Supreme political authority provided the basis for challenging Western hegemony and reclaiming former Soviet lands. Ever since he came to power, Putin has been obsessed with recreating the boundaries of the Soviet Union as Russian territory. In 2005, he told the world that the collapse of the Soviet Union ‘was the greatest geopolitical catastrophe of the century’ and a ‘genuine tragedy’ for the Russian people as ‘tens of millions’ of Russians found themselves outside Russian territory (BBC 2005). His strategic view of the world is a throwback to the Concert of Europe of the nineteenth century in which the great powers had vested interests and spheres of influence, intervened in the internal affairs of small states and acted collectively to maintain a balance of power or security in Europe. Such a system is antithetical to the current multilateral norms and arrangements that seek to curb unilateralist behaviour by states. The US and its Western allies did not only refuse to dismantle NATO, they proceeded to expand it to include former Soviet republics and East European countries. This was a strategic blunder of enormous proportions, especially as Putin wanted Russia to join the alliance but was told that he had to apply like any state seeking membership (Rankin 2021). Hubris or triumphalism clouded Western strategic policy-making. Many bought the dubious and self-serving idea of the end of history—that markets and democracy would now determine how states are governed, and that the US would be the only superpower and would do as it pleased in policing the world. This posture fuelled Putin’s suspicion that the West still regarded Russia as an enemy and was not serious about world peace. In the logic of realpolitik and national security, the borders of states, especially those of great powers, should be free of antagonistic military forces. It is highly unlikely that Estonia and Latvia, which share a common border with Russia, would have been allowed to join NATO if Russia had regained its confidence and was governed by a resolute and calculating leader like Putin. Matters were not helped when NATO signalled that it would consider Ukraine’s membership of the alliance. There are two key planks in Putin’s strategy to revive Russia’s power. The first is his challenge of liberal values and the rules-based multilateral system. It must be stressed that the attack on liberalism is not just a Russian problem. The US and its allies ignored UN rules and procedures in 2003 by invading Iraq under the false pretence of looking for weapons of mass destruction. And there have been countless other US interventions in foreign countries that clearly violated the rules-based international order, including the use of lethal drone strikes in Pakistan and Arab countries. In his United States of War: A Global History of America’s Endless Conflicts, from Columbus to the Islamic State (2020), David Vine observes that the US ‘has been at war or has invaded other countries almost every year since its independence’. Liberal values have also eroded in the US, where there was an attempt in January 2021 to prevent a transfer of power to the winner of the presidential election, and laws are being passed in Republican-controlled state legislatures to limit black participation in the electoral process and overturn election results. Putin’s anti-liberalism is, however, visceral or an article of faith and serves as an instrument for resurrecting Russian power. In this regard, Russia has emerged as a leading actor in disinformation, cyberattacks and tampering with the electoral processes of Western and other democracies. Russia’s hacking of Hilary Clinton’s and the Democratic National Committee’s emails, and its collusion with Wikileaks to influence the 2018 elections in favour of Donald Trump, another leader with an authoritarian mindset, is instructive. It is clear from Putin’s pronouncements that he is unhappy with the post-Cold War security arrangements and the global rules-based liberal order, which he believes shackle his quest for global power. The second plank of Putin’s strategy is to claw back lost territories along Russia’s border. The vehicle for realising this strategy is the 25 million ethnic Russians who reside in the new ex-Soviet countries. The creation of the Soviet Union in 1917 was accompanied by the Russification of non-Russian republics, through a process that involved the deportation of large numbers of disloyal individuals from indigenous populations and the encouragement of Russians to migrate and fill gaps in labour markets and public administrations. One of the most glaring examples of Russification was the displacement of the German population in Kaliningrad (which does not even share a border with Russia but is wedged between Lithuania, Poland and the Baltic Sea) and the massive migration of Russians into the region after Germany’s defeat in the Second World War. Joseph Stalin occupied, demanded and was given the right to annex Königsberg (the previous name of Kaliningrad) by the Allied Powers as compensation for the mass suffering Russians had been subjected to by Nazi Germany. Winston Churchill, the British prime minister, supported the expulsion (ethnic cleansing) of Germans from Königsberg. In his words, ‘expulsion is the method which, in so far as we have been able to see, will be the most satisfactory and lasting. There will be no mixture of populations to cause endless trouble’ (Sukhankin 2018: 41). In 1945, there were only 5,000 Russians and more than 100,000 Germans in Königsberg; by 1948 about 400,000 Soviets had moved into the region. There are now only 1,600 Germans or about 0.4 per cent of the population; Russians currently account for 87 per cent of the population (Wikipediaa). After the collapse of the Soviet Union, Ukraine had the largest number of ethnic Russians (about 8,300,000, or 17.2 per cent of the population), followed by Kazakhstan (3,600,000, or 20.2 per cent of the population), Belarus (785,000) and Uzbekistan (750,000). However, Latvia (487,250, or 25.2 per cent of the population) and Estonia (322,700, or 24.2 per cent) have higher percentages of ethnic Russians than all other countries (Wikipediab). Relations between ethnic Russians and host nations are often tense as the latter seek to undo historical injustices. I observed in 2004 the deep animosity between Latvians and ethnic Russians when I organised an UNRISD conference in Riga, the capital (with the UNDP office in Latvia acting as hosts), to discuss the findings of our multi-country research project on Ethnic Inequalities and Governance of the Public Sector. The current Latvian deputy prime minister and defence minister, Artis Pabriks, who was a researcher at the time, conducted the Latvian study. Memories of the 60,000 or more Latvians deported to Siberia by Soviet leaders just after the Second World War were still fresh among Latvians, who also disliked the fact that Russians constituted the majority population in their capital city. Russians, on the other hand, complained about language laws and tough citizenship rules that made it difficult for Russians to obtain citizenship under the new government. Putin has used the agitation of ethnic Russians for equal treatment as a basis for invading the new territories. The forerunner to the invasion of Ukraine was Russia’s intervention in the conflict in 2008 in Abhkazia and South Ossetia, in Georgia, in which Russia supported and later recognised the two breakaway territories from Georgia. Despite the very small number of ethnic Russians in those territories, residents there now carry Russian passports. The big prize is Ukraine, which Putin regards as a spiritual and cultural home for Russians and which, as we have seen, hosts the largest number of Russia’s diaspora. The pattern for annexation is clear: ethnic Russians complain about discrimination and declare independence in their localities, the Russian army is sent in to defend them, the Russian Parliament recognises the breakaway territories, and Putin formalises the process by incorporating the territories into Russia. The popular uprising in 2014 against the Ukrainian president, Viktor Yanukovych (who was critical of Ukraine’s application to join the EU), his removal from office and subsequent exile to Moscow may have been a turning point for Putin. The first invasion of Ukraine was in 2014 in Crimea, where ethnic Russians account for 65 per cent of the population. The failure of the Western powers to draw a line on Crimea emboldened Putin to mount a second invasion of the country. Again, as in the first invasion, ethnic Russians complained about maltreatment, they seized Donetsk and Luhansk in the Donbas region, where they constitute a majority, the Russian military rendered support, Russia’s Parliament recognised their autonomy and Putin sent in the military for a full invasion, which, this time, may involve the annexation of the entire country. Russia’s strategy for the countries bordering its southern border, which are less antagonistic, involves the creation of a regional alliance (the Collective Security Treaty Organisation) of Russia, Armenia, Belarus, Kazakhstan, Kyrgyzstan and Tajikistan, and turning these countries into puppet states. This allowed Russia to send troops to oil-rich Kazakhstan in January 2022 to put down anti-government protests. The other non-Soviet country on Russia’s southern border, Mongolia, relies on Russia to counter Chinese threats to its territory. The two-plank strategy of disdain for the liberal rules-based world order and the annexation of ex-Soviet republics is underpinned by a policy of reducing Russia’s economic dependence on the West in order to be able to withstand sanctions. The Economist (2022) reckons that Russia has reduced its debt to just 20 per cent of GDP, built formidable reserves of USD 620 billion and created a ‘fortress economy’. The extent to which such measures will insulate the Russian economy, and the appetite of its nomenklatura and oligarchs for Western goods and services, from the current raft of Western sanctions remains to be seen. Implications for Africa Russia’s mission to upend the liberal rules-based multilateral order suggests a lack of confidence in its ability to use those rules to catch up with the West. Playing rogue is the weapon of great powers in decline. In this regard, Russia’s behaviour contrasts sharply with that of China, a rising economic and technological powerhouse, which seeks to use—not disrupt—the existing global arrangements to challenge Western hegemony and attain its goal of superpower status. Russia is not even among the top ten largest economies in the world: its GDP of USD 1.4 trillion is dwarfed by those of the US (about USD 20 trillion) and China (USD 14 trillion). Russia’s GDP equals that of Brazil but lags behind India and even the Republic of Korea, with a population of only 50 million. Despite a few pockets of excellence and an educated workforce, Russia is also outmatched in the technological field: it spends just 1 per cent of its GDP on research and development; its corporations conduct little or no research; and the country as a whole trails China, the US, Japan, Korea, Germany and India in patent applications. Its technological strength is in near-space exploration, rocket engines and military hardware; however, research suggests that there have been hardly any spillovers from such sectors into the civil sphere (Sanghi and Yusuf 2018). While Russia is an economic dwarf, it ranks second to the US in the global firepower index, or military capability (Armstrong 2022) and has the largest number of nuclear warheads in the world—6,257 to the US’s 5,500 and China’s 350 (World Population Review 2022). This asymmetry between military power and economic and technological prowess may explain Putin’s infatuation with military might and willingness to use it to assert Russia’s status as a global power. The wide-ranging sanctions recently imposed on Russia suggest that the West is willing to stand up to Russia by isolating it from vital areas of global finance, trade, investment, technology, entertainment and travel. The scale of the sanctions is unprecedented. We may well be witnessing the return of the Iron Curtain, which may plunge Europe into protracted instability as Russia fights back to break free from isolation. It is highly unlikely now that Ukraine will be admitted into NATO. However, the invasion has given NATO a new lease of life and produced an outcome that Putin wanted to prevent: NATO troops and potential instability on Russia’s western border. Neutral Western countries like Sweden, Finland, Ireland and even Switzerland may abandon their longstanding policy of neutrality and seek NATO membership for protection. Remarkably, the decision of Sweden and Switzerland to fully participate in the Western sanctions makes them vulnerable to Russian retaliation if they remain outside the military alliance. The doctrine of spheres of influence undermines the security of small nations The invasion and unfolding geopolitical crisis have serious implications for Africa. Three stand out in bold relief. The first is the danger of reinstitutionalising the doctrine of spheres of influence in the governance of the world system. Putin regards the territories of the former Soviet republics as ‘historical Russian land’, which suggests that Russia has the right to take them back or intervene in them to get the leaders of those countries to submit to Russian demands. Putin’s address to the world on the day of the invasion is telling. In that long and rambling speech, he asserted that ‘The problem is that in territories adjacent to Russia, which I have noted is our historical land, a hostile anti-Russia is taking shape’1. This statement suggests that Latvia, Estonia, Belarus, Ukraine, Georgia, Azerbaijan and Kazakhstan belong to, and will always be contested by, Russia. Part of Putin’s problem of seeing ex-Soviet republics as Russian territory is that the Russian empire was the only empire in Europe that survived the First World War. The Ottoman, Austro-Hungarian and German empires all collapsed in 1918 and a host of new nations were born. The Russian empire was simply transformed into the Union of Soviet Socialist Republics when the Bolsheviks took power in 1917. However, the fact that the ex-Soviet republics have enjoyed only three decades of independence doesn’t mean they should lose it against their will. Big powers have historically carved out areas that they regard as spheres of influence. The Monroe Doctrine, for instance, informed the foreign policy of the US for much of the nineteenth and twentieth centuries. Under this doctrine, the US viewed efforts by European powers to influence or control countries in the Americas as a threat to US security. In exchange, the US agreed to not interfere in the affairs of Europe and its colonies. When, in 1962, Nikita Khrushchev, the Soviet leader, decided to station nuclear weapons on Cuban soil, just 145 kilometres (90 miles) off the coast of the US, John Kennedy saw it as an act of war and threatened to take them out by blockading Cuba. Khrushchev caved in and Kennedy agreed to not invade Cuba. As imperial powers, the foreign policies of France, the UK and Portugal have also been driven by notions of spheres of influence. Britain struggled to maintain control of its ex-colonies after it agreed to give them independence; it created the Sterling Area and Commonwealth system to defend the waning international role of the pound sterling. Under this system, it tried to compel the newly independent countries to retain the colonial currency boards instead of creating central banks, maintain their reserves in the UK treasury, tie their currencies to sterling and pursue extremely restrictive fiscal policies (spending only what they earned as foreign exchange) in exchange for the UK directing its investments, trade and aid flows towards them (Bangura 1983). And through the franc zone, France continues to exercise considerable control over the monetary policies of the Francophone African countries and regards those countries as part of its sphere of influence. It intervenes regularly in those countries to change or prop up regimes; for example, it currently has 3,500 troops in Mali under the guise of fighting Islamist militants. Even during the Ebola crisis, Western assistance to the three West African countries affected by the virus (Sierra Leone, Liberia and Guinea) followed a spheres-of-influence logic, with the UK heavily involved in Sierra Leone, the US in Liberia and France in Guinea (Abdullah and Rashid 2017). The doctrine of spheres of influence has no place in the UN charter or international law. Indeed, the raison d’être of the UN (and its antecedent, the League of Nations) was to outlaw the quest for spheres of influence in world politics. The fundamental principles of the UN are the prohibition of force in settling disputes unless when sanctioned by the Security Council or for self defence; acceptance of the sovereignty, territorial integrity and equality of all member nations; and respect for freedom and human rights. These principles seek to outlaw war in the conduct of international relations. Despite their violation in many instances, they remain important for small states that do not have the resources to confront strong nations. Indeed, resistance to the doctrine of spheres of influence and military alliances informed the decision by developing countries to form the Non-Aligned Movement during the Cold War. Most developing countries still regard these principles as sacrosanct. It is not surprising that the overwhelming majority of developing countries (111) voted for the UN General Assembly resolution that ‘deplores in the strongest terms the aggression by the Russian Federation against Ukraine’, and called on Russia to ‘immediately, completely and unconditionally withdraw all of its military forces’. If Putin’s blatant attempt to relegitimise the doctrine of spheres of influence is allowed to stand, what will stop the former European imperial powers from affirming their right to intervene regularly in Africa, and even recolonise a few countries, by arguing that they created those countries in Berlin in the nineteenth century? How a beleaguered Russia is likely to behave in Africa The second issue is how a beleaguered Russia is likely to behave in Africa. If the West’s sanctions bite and Russia finds itself excluded from much of the European social, economic and political space, it is likely to become more paranoid and confrontational and would aggressively seek allies in non-Western regions, including in Africa. Africa’s open, fragmented, underdeveloped and contested policy space makes it a strong candidate for enhanced Russian intervention, big power politics and the creation of spheres of influence. Russia’s engagement with Africa will be substantially different from Soviet engagement with it during the Cold War. During the Soviet era, Russia had a progressive, anti-Western or anti-imperialist policy: it stood in solidarity with African countries in fighting European colonial domination and the obnoxious racist regime of apartheid South Africa. It provided technical, educational and financial aid as well as military assistance to many countries. And it did not associate itself with kleptocratic and bloody military regimes like those of Idi Amin of Uganda, Jean-Bédel Bokassa of Central African Republic, Mobutu Sese Seko of Zaire or Samuel Doe of Liberia, which were nurtured or supported in varying degrees by Western powers. Russia served instead as an inspiration to forces across Africa that were interested in transformative social change, even though in Ethiopia, Mozambique and Angola, where attempts were made to implement the Soviet model of development, it turned out to be a disaster. A beleaguered, authoritarian, economically weak, rent-seeking capitalistic Russia that has been stripped of its aspirational ideology will be different. The current Russia will be highly transactional, aggressive and opportunistic. Russia’s recent attempts to revive its flagging relations with African countries are instructive. Given its weak economy, it will not be a strong competitor in productive investments, trade and aid compared to China, the EU and the US. Russia’s exports to Africa amounted to a mere USD 13 billion in 2019, and its foreign direct investment was estimated to be less than 1 per cent of Africa’s total FDI stock in 2017 (Irwin-Hunt 2020). This is a pittance compared to China’s FDI stock of USD 110 billion in Africa (Yu 2021) and China’s USD 250 billion trade with Africa. Russian companies in Africa have largely focused on the extractive sector—such as diamonds, nickel, manganese, oil and gas—as well as nuclear energy, where they have a comparative advantage. Even though Russia is rich in mineral resources, it lost many of those resources to the new states after the dissolution of the Soviet Union. It is believed that importing raw materials from Africa is cheaper than extracting them from Russia’s remote regions that provide the bulk of its resources (Arkhangelskaya and Shubin 2013). Increased Russian involvement in Africa’s extractive sector, which has a history of corruption, bad deals and illicit transfers, is unlikely to be different from the West’s, and recently China’s, pillage of the continent’s resources and impoverishment of its people. In Honest Account 2017, Global Justice Now (2017) reported that, in 2015, Africa as a whole was a net creditor to the rest of the world (largely Western countries) by USD 41.4 billion. In other words, more resources (USD 203 billion—through tax avoidance, debt payments and resource extraction) were taken out of the continent than flowed in (USD 161.6 billion—through loans, remittances and aid). The Thabo Mbeki-led African Union-Economic Commission for Africa’s (2005) own report estimated that USD 50 billion left Africa as illicit financial flows every year. And War on Want (2016) reported that about 100, mostly British, companies listed on the London Stock Exchange controlled more than USD 1 trillion worth of resources in just five commodities—oil, gold, diamonds, coal and platinum—and a quarter of those companies are registered in tax havens. Russia’s quest for raw materials may spur enhanced greed and dirty tricks as it tries to compensate for lost opportunities in the West. This may aggravate Africa’s resource drain. Russia is also likely to push African countries to transition to nuclear energy, where it has a huge advantage, citing the continent’s large deficit in power generation. About 600 million Africans are estimated to be without access to electricity. Nuclear energy was one of the agenda items in the 2019 Russia-Africa Summit in Sochi, attended by 42 African leaders. Russia is in negotiations with most North African countries, Ethiopia, Nigeria, Ghana, Zambia and Rwanda to sign nuclear energy deals, and has committed to provide 80 per cent of the funds to build Egypt’s first nuclear power plant for a whopping USD 25 billion (Chimbelu 2019). However, Russia has a poor record in large-scale infrastructure projects. Despite Nigeria sinking more than USD 10 billion into the Ajaokuta iron and steel project, the Russian company, TyazhPromExport, contracted to build the plant in 1976 failed to produce any steel before the project was abandoned in 1994. The failure of the Ajaokuta steel project was a huge blow to Nigeria’s quest for industrialisation. Nuclear reactors are expensive, capital-intensive, take years to build, and have high maintenance and safety costs. African countries should be wary of incurring unsustainable debts and permanent dependence on Russia to run and maintain reactors. It is not surprising that South Africa cancelled its agreement with Russia for a second nuclear plant in 2017, citing cost, after an environmental group successfully challenged the government in court. Surely, there must be cheaper and safer green energy alternatives—such as solar, hydro and wind power—to nuclear reactors in solving Africa’s electricity problem. A beleaguered Russia is also likely to be heavily involved in the internal politics of African countries. Such intervention will be seen primarily through the prism of its conflict with the West and its need to secure whatever resources and economic opportunities it can get as it tries to evade sanctions and diversify its stuttering economy. Democratic norms and practices have not fared well in Africa after the wave of democratisation that ended military and one-party rule in much of the continent in the 1990s. There has been a serious democratic regression as incumbents in many countries change their constitutions to extend their rule, governing parties capture state institutions, harass opposition parties and restrict the rights of citizens, and elections are rigged to prevent a transfer of power. By 2020, term limits had been modified or eliminated in 16 African countries (Siegle and Cook 2020), and in a list of controversial elections in the world, 50 are African (Wikipediac). Such setbacks in democratisation, security challenges and failure to improve the lives of citizens have encouraged the military to make a comeback in African politics (Ibrahim 2022). Military coups have occurred in Mali, Burkina Faso, Guinea, Sudan and Chad in the last two years. While Western powers have been opportunistic in advancing the democracy agenda in Africa (punishing countries they dislike while giving a pass to others until there is a breakdown of order), they have joined African regional organisations, which have failed to hold flawed democracies to account, to oppose the return of military rule on the continent. Russia has stepped in to prop up besieged African dictators by providing arms and military protection. Its state-owned arms export agency, Rosoboronexport, is the largest arms exporter to Africa, accounting for about 50 per cent of Africa’s arms imports. It is the second largest arms exporter in the world after the US. Indeed, the armament sector plays a big role in Russia’s economy as it accounts for a large proportion of manufactured exports (Chatham House 2017). Algeria and Egypt are Russia’s biggest clients in Africa, but it has recently expanded sales to a number of sub-Saharan African countries, including Nigeria, Tanzania, Cameroon, Angola and the Central African Republic (Episkopos 2020). Russia uses its paramilitary or mercenary outfit, the Wagner Group, which specialises in counterinsurgency and counterterrorism training as well as use of military hardware, to challenge Western power in Africa and provide security to rogue African leaders who want to remain in power and roll back democratic change. In exchange, Russia receives concessions to extract mineral resources, commercial contracts or access to ports and airbases (Fasanotti 2022). The Wagner Group is active in the Central African Republic, where it has been accused of summary executions, torture and indiscriminate targeting of civilian facilities (Parachini and Bauer 2021), Sudan (especially during Omar Al-Bashir’s regime), Mozambique, Madagascar, Libya, Chad, Mali and Burkina Faso. There has been a standoff between France and Mali, where French troops have been unable to beat back Islamist terrorists despite committing 3,500 troops there since 2013. Faced with pressure from France, its European allies and African regional organisations to organise elections for a transition to civil rule, the military leader, Assimi Goita, invited the Wagner Group to bolster his security and declared the arrogant and pushy French ambassador persona non grata. We are likely to see an aggravation of this kind of big-power competition in Africa in which Russia and willing African dictators try to beat back pressure for democratisation and the protection of human rights. Western governments may also be forced to give up all pretence of promoting democracy in Africa and may relate with countries primarily from the strategic perspective of countering Russian and Chinese penetration of the continent. It is indeed astonishing that although 25 African countries supported the General Assembly resolution that called on Russia to withdraw its troops from Ukraine, 17 countries abstained, eight did not vote and one voted against. Russia provides security through its Wagner Group to many of the states that abstained or stayed away, others are under sanctions themselves, and some have bilateral military co-operation agreements with Russia. It is important to understand that Western powers became interested in the global democracy project only after the collapse of the Soviet Union. For much of its history, the West practised democracy at home and realpolitik or pragmatism, as defined by its strategic and economic interests, overseas. This meant it could use force to achieve its objectives without following UN rules or international law and work with all kinds of despots and corrupt leaders whose interests were aligned with its own. Its cosy relations with the despotic regimes of the Gulf oil states underscore the latter point. Western powers failed to sanction or hold to account the Saudi Arabian leadership after the Saudi Arabian journalist, Jamal Khashoggi, was butchered by Saudi officials at the Saudi embassy in Istanbul in 2018. Britain tried to use democracy as a tool to stagger its exit from its colonies in the 1950s and part of the 1960s, while devising new methods of influence and control, such as the Sterling Area system and the Commonwealth—but this was only for a brief period. France did not bother with the idea of injecting democracy into its decolonisation project, and Portugal was chased out of its colonies through armed struggles. Let us be clear: the belief that the US had become the only superpower in town after the collapse of the Soviet Union encouraged the West to cloak its global strategic interests with the ideals of democracy. We may be heading back to the stark days of authoritarian politics of the pre-1990s. It is difficult to believe that the West will firm up its already questionable commitment to democracy on the continent when faced with challenges from Russia and China, which have no interest in democracy. Short-term costs of the crisis One final issue that should be highlighted in discussing the invasion and how it is likely to impact Africa is the short-term effects of the rise in oil, gas and wheat prices. Russia is the world’s second largest exporter of oil after Saudi Arabia; it is also the fourth largest gas exporter after the US, Qatar and Algeria. And both Russia and Ukraine are major wheat producers, with Russia ranked third in the world after China and India, and Ukraine seventh. Both Russia and Ukraine account for 30 per cent of global wheat exports, and Ukraine is a major exporter of maize and vegetable oil. South Africa, for instance, imports about 30 per cent of its wheat from Russia and Ukraine, and Russia is the second largest exporter of wheat to Nigeria. Supply chains in commodity production and marketing are often disrupted during global crises. It is not surprising that the prices of oil, gas, wheat and other grains, which were already rising in late 2021, have skyrocketed since the invasion. The effects of price rises depend on whether a country is a net exporter or importer. For the big oil producers, such as Nigeria, Angola, Gabon, Libya, Algeria, Republic of Congo, Ghana, Equatorial Guinea and Chad, the price increase in oil is likely to be a boon as state revenues will increase, especially if production is ramped up. Gas producers like Nigeria, Algeria, Egypt, Libya, Angola and Equatorial Guinea may also take advantage of the cancellation of the Russo-German Nord Stream 2 oil pipeline if they can invest in the infrastructure for supplying gas across the Mediterranean into Europe (Iyora 2022). However, the vast majority of African countries do not produce oil or, if they do, are net importers. For these countries, the global oil price hike has translated into a sharp rise in the prices of petrol and related products as well as increases in transport fares. A similar problem can be observed with grain. The important wheat producers in Africa are South Africa, Kenya, Ethiopia, Sudan, Tanzania, Zimbabwe, Zambia and Nigeria. However, all these countries are net importers. While the rise in wheat prices may improve the incomes of local farmers, it may hurt consumers as bread, pasta, noodles, biscuits and cakes become expensive. Conclusion Russia’s invasion of Ukraine and the current standoff between Russia and the West threaten world peace. The doctrine of spheres of influence, which informs Putin’s invasion, is dangerous not only for former Soviet republics but also for African countries and other small nations around the world. It provides a justification for redrawing boundaries, annexing countries and undermining the territorial integrity of states, which is a fundamental principle of the UN. The isolation of Russia through the West’s punitive sanctions may not only adversely impact Africa through oil, wheat and other grain price hikes, it may also create a Fortress Russia that will pursue an aggressive policy in Africa and other weak regions in order to gain allies, markets and raw materials and diversify its external relations. This is likely to impact African politics negatively as equally beleaguered African politicians who do not want to give up power may sign up for Russian protection. In this new dynamic, Western countries may be forced to abandon their already questionable support for Africa’s troubled democracy project and engage with African countries through the prism of their rivalry with Russia. The insistence of the West on maintaining NATO’s open-door policy of admitting any country that seeks to join the alliance is dumb. Putin should withdraw from Ukraine and Ukraine should not be admitted into NATO. The Cold War arrangements that kept Finland, which shares a border with Russia, out of the military alliances of NATO and the Warsaw Pact, while allowing the country to thrive as a Western social democracy provide useful lessons. While the doctrine of spheres of influence should be rejected unreservedly, the security interests of all states that do not threaten the territorial integrity of other states should be respected. Putin seems to have overplayed his hand. The West cannot win a war against him because of his nuclear arsenal, but his economy can be crippled and the three decades of his citizens’ exposure to, and enjoyment of, Western lifestyles and contacts can be disrupted, fuelling resentment and possibly instability in his country. The invasion has done profound damage to Russia’s relations with the West, which will be difficult to reverse as long as Putin and like-minded people around him are in power. Africa should brace itself for the challenging years ahead. Yusuf Bangura was a Research Coordinator at the United Nations Research Institute for Social Development (UNRISD) from 1990 to 2012. He was the lead author of the UNRISD flagship report Combating Poverty and Inequality: Structural Change, Social Policy and Politics (UNRISD 2010) and Series Editor of Ethnic Inequalities and Governance of the Public Sector, and Developmental Pathways to Poverty Reduction (both series published by Palgrave Macmillan and UNRISD). In 2013-14, he taught international political economy at Fourah Bay College, University of Sierra Leone. Note Address by the President of the Russian Federation, 24 February 2022. References Abdullah, I. and Rashid, I., eds, 2017, Understanding West Africa’s Ebola Epidemic: Towards a Political Economy, London: Zed Books. African Union-Economic Commission for Africa 2015, Illicit financial flows: Report of the High Level Panel on Illicit Financial Flows from Africa, Addis Ababa. Arkhangelskaya, A. and Shubin, V., 2013, Russia’s Africa Policy, Occasional Paper No. 157, South African Institute of International Affairs. Armstrong, M., 2022, Armed Forces, The World’s Most Powerful Militaries, Statista, 14 January. Bangura, Y., 1983, Britain and Commonwealth Africa: The Politics of Economic Relations, 1957–75. Manchester: Manchester University Press. BBC, 2005, Putin deplores collapse of USSR, 25 April. http://news.bbc.co.uk/2/hi/4480745.stm Chatham House, 2017, Russia’s Role as an Arms Exporter: The Strategic and Economic Importance of Arms Exports for Russia, Research Paper, 20 March. Chimbelu, C., 2019, African countries mull nuclear energy as Russia extends offers, DW World News, 22 October. Crotty, J., 2020, Russia’s post-Soviet transition offers warning on hidden unemployment coronavirus furlough schemes, The Conversation, 1 July. Episkopos, M., 2020, Russia Is Ramping Up Arms Exports To Africa? The National Interest, 8 September. Fasanotti, F. S., 2022, Russia’s Wagner Group: Influence, commercial concessions, rights violations, and counterinsurgency failure, Brookings Initiative on Nonstate Armed Actors, 8 February. Gould-Davies, N. and Woods, N., 1999, Russia and the IMF, International Affairs, Vol. 75, 1, pp. 1–21. Global Justice Now, 2017, Honest Account 2017—How the world profits from Africa’s wealth, 24 May, https://www.globaljustice.org.uk/resource/honest-accounts-2017-how-world-profits-africas-wealth/ Ibrahim, J., 2022, African Politics: Return of the Military, Premium Times, 28 January. Irwin-Hunt, A., 2020, Russia’s Ongoing Charm Offensive in Africa, FDI Intelligence, Financial Times, 15 September. Iyora, F., 2022, Can African Gas replace Russian supplies to Europe? Al Jazeera, 1 March. McFaul, M., 2021, Russia’s Road to Autocracy, Journal of Democracy, Vol. 32, Issue 4, pp. 11–26. Parachini, J.V. and Bauer, R., 2021, What Does Africa Need Most Now: Russian Arms or Good Vaccines? The Rand Blog, https://www.rand.org/blog/2021/11/what-does-africa-need-most-now-russian-arms-sales-or.html Rankin, J., 2021, Ex-NATO Head says Putin Wanted to Join Alliance Early on in His Rule, The Guardian, 4 November. Sanghi, A. and Yusuf, S., 2018, Russia’s Uphill Struggle with Innovation, Washington, DC: The World Bank, 7 September. Siegle, J. and Cook, C., 2020, Circumvention of Term Limits Weakens Governance in Africa, Africa Centre for Strategic Studies, 14 September, https://africacenter.org/spotlight/circumvention-of-term-limits-weakens-governance-in-africa Sukhankin, S., 2018, Bridge To Nowhere: Kaliningrad On Geopolitical Map Between Russia And Europe, PhD thesis, Department of Modern and Contemporary History, Universitat Autonoma de Barcelona. The Economist, 2022, A grim look out, 19 February. Vine, D., 2020, United States of War: A Global History of America’s Endless Conflicts, From Columbus to the Islamic State, Berkeley, CA: University of California Press. War on Want, 2016, The New Colonialism: Britain’s scramble for Africa’s energy and mineral resources, https://waronwant.org/resources/new-colonialism-britains-scramble-africas-energy-and-mineral-resources. Wikipediaa, Kaliningrad, https://en.wikipedia.org/wiki/Kaliningrad Wikipediab, Ethnic Russians in Post-Soviet States, https://en.wikipedia.org/wiki/Ethnic_Russians_in_post-Soviet_states Wikipediac, List of Controversial Elections, https://en.wikipedia.org/wiki/List_of_controversial_elections World Population Review, 2022, Nuclear Weapons by Country, 2022, https://worldpopulationreview.com/country-rankings/nuclear-weapons-by-country Yu, S. Z., 2021, Why Substantial Chinese FDI is Flowing into Africa, LSE Blog, 2 April, https://blogs.lse.ac.uk/africaatlse/2021/04/02/why-substantial-chinese-fdi-is-flowing-into-africa-foreign-direct-investment/